Petlab: New Zealand's national rock catalogue and geoanalytical database. Issue 3 (2nd July 2016) - Strong, DT; Turnbull, RE; Haubrock, S; Mortimer, N
ABSTRACT: The Petlab database is New Zealand's online national rock and analytical database, and provides an accessible, structured and permanent data repository for the local and global geoscience communities. The database contains locations, descriptions and analyses of rock and mineral samples from onland New Zealand, the offshore New Zealand region, Antarctica and worldwide. It is operated by GNS Science and, as a nationally significant database, currently receives core funding from central government. The major data contributors are GNS Science and Auckland, Massey, Waikato, Victoria, Canterbury and Otago universities, all of whom use the database as a digital catalogue for their rock and mineral collections. Petlab sample information and geoanalytical data can be uploaded, queried, viewed and downloaded athttp://pet.gns.cri.nz . Petlab is a valuable tool for geoscientists in research and industry.